Perancangan Gardu Distribusi Pengembangan Perumahan Green Nurhidayat Romang Polong - Herman Nawir; Muhammad Ruswandi Djalal; Muh. Yusril Hamma (Politeknik Negeri Ujung Pandang, 2021)
Green Nurhidayat Romang Polong Residence is a new housing located Samata’s axis road. In the housing development process, an electrical system is something important to supply electrical power in the housing. The distribution of electricity cannot be separated from the distribution substations. This research was conducted to design distribution substations. This research aims to determine the equipment and determine the capacity of each equipment. This research begins with observation, collects the data and data analysis. Data was collected through document study, observation and interview methods. Based on the results of research, distribution substations on Green Nurhidayat Romang Polong Residence used portal type substation with a transformer with a capacity of 400 kVA. The safeguards used are Lightning Arrester has a capacity of 24 kV, 5 kA, Fuse Cut Out with safety capacity of 12.5 A, the conductor area used to connect the Transformer to low voltage panel is a NYY type cable with a cross-sectional area of 4 (1 x 400 mm2 ), the conductor on the primary side that connects low voltage grid to Ligtning Arrester and Lightning Arrester to a transformer is AAAC type cable with a cross-sectional area of 35 mm2, while on the low-voltage grid, NFA2X type cable with a cross-sectional area of 3x70 mm is used. Low voltage panel divided into line, circuit breaker with a safety capacity of 700 A, NH Fuse with a capacity of 224 A and a rod electrode with a length of 5 m on the grounding system.